Cost-benefit analysis (CBA) of health and safety regulations - Bernhard Tröster; Rudiger Von Arnim; Werner Raza (Hans-Böckler-Stiftung, 2024)
Even though trade negotiations have increasingly come to focus on regulatory issues, the full impacts, that is, both social costs and benefits of regulatory changes, often remain unexamined in trade impact assessments. To bridge this gap, we scrutinize the theoretical foundations, methodologies and policymaking applications of cost-benefit analysis (CBA) in the context of health and safety regulations. CBA has become the main approach in economics to quantify the social costs and benefits of regulation. Gaining a thorough understanding of CBA processes, their applications and their limitations provides a valuable foundation for our upcoming research, the integration of the broader impacts of regulations into a global trade model.
Keywords: 330; non-tariff barriers; globalisation; international treaties; free-trade agreeements